Smart Power to the People: Business Models for Engaging Domestic Energy Users in Smart Local Energy Systems in Britain - Fuentes-Gonzalez, F (Elsevier Ltd, 2024)
Smart Local Energy Systems (SLES) are proposed as a method of decarbonising energy systems that uses demand management by energy users to integrate intermittent renewables. SLES therefore require the increasingly active participation of energy users in the operation of energy systems. We spoke to operators and developers of existing local energy systems in Britain today, to understand their business models, and how they interact with users. We find that users are seen as critical to the effective operation of local energy systems. Operators support users to play this role, either through providing advice, or through minimising the amount of adapting to new technologies and techniques users are required to do. Often these users are physically connected to the local energy system, and cannot easily switch to a different system. As widespread deployment of SLES will require the participation of domestic users who currently can easily switch suppliers, better user engagement is a key challenge for SLES. We ran two workshops with local energy system stakeholders to develop business models to address this challenge. We present two outline business models designed to provide increased consumer protection and support to SLES users. We draw on the literature on smart energy users to analyse existing systems and our outline novel business models, discussing the conceptualisation of users that underpins them, their governance and potential conflicts of interest, and who they create value for. We end with suggestions for policy to maximise the potential of these business models to provide socially equitable access to SLES. © 2024 The Authors